A Course on "Health Management in Crises" for Medical Students: A Delphi Study - Yadolah Zarezadeh; Haidar Nadrian; Golakeh Karimi; Tayeb Ghadimi; Fayegh Yousefi; Arash Pooladi; Arezoo Yari (Tabriz University of Medical Sciences, 2017)
Background: General physicians play a significant role in the health management of crises. In order to enhance the knowledge and skills of medical students on how to address health-related issues in crises and to promote their ability to manage and deal with such crises after graduation, appropriate training is necessary. Methods: Applying the Delphi method, 103 experts with field experience in health management and crises were invited to participate in the study. The Delphi study provided aggregation of the opinions and extracted the topics. Conventional content analysis was used to make sense of qualitative data gathered during the study. Results: Among the feedback (n = 66) obtained in the first round, a primary list was extracted including 27 topics and 97 single items. Nineteen major topics, encompassing 97 items, were finally determined in the subsequent rounds. The participants agreed to teach this course at the beginning the internship period via different methods of instruction. Conclusion: This study indicated that health management in crises is important and must be taught in medicine. This study provided a blueprint and an educational rationale as well as contents and structure of a course on health management in crisis to be delivered in undergraduate medical education.